The course of patients with Chagas heart disease during episodes of decompensated heart failure. (17th February 2021) - Issa, Victor Sarli; Ayub‐Ferreira, Silvia Moreira; Schroyens, Matthew; Chizzola, Paulo Roberto; Soares, Paulo Rogerio; Lage, Silvia Helena Gelas; Bocchi, Edimar Alcides
Abstract: Aims: This study aimed to analyse the clinical presentation and prognosis of patients with Chagas cardiomyopathy and decompensated heart failure (HF), as compared with other aetiologies. Methods and results: A prospective cohort of patients admitted with decompensated HF. We included 767 patients (63.9% male), with median age of 58 years [interquartile range 48.2–66.7 years]. Main aetiologies were non‐Chagas/non‐ischaemic cardiomyopathies in 389 (50.7%) patients, ischaemic disease in 209 (27.2%), and Chagas disease in 169 (22%). Median left ventricular ejection fraction was 26% (interquartile range 22–35%). Patients with Chagas differed from both patients with non‐Chagas/non‐ischaemic and ischaemic cardiomyopathies for a higher proportion of cardiogenic shock at admission (17.8%, 11.6%, and 11%, respectively, P  < 0.001) and had lower blood pressure at admission (systolic blood pressure 90 [80–102.5], 100 [85–110], and 100 [88.2–120] mmHg, P  < 0.001) and lower heart rate (heart rate 71 [60–80], 87 [70–102], and 79 [64–96.5] b.p.m., P  < 0.001). Further, patients with Chagas had higher serum BNP level (1544 [734–3148], 1061 [465–239], and 927 [369–1455] pg/mL, P  < 0.001), higher serum bilirubin (1.4 [0.922.44], 1.2 [0.77–2.19], and 0.84 [0.49–1.45] mg/dL, P  < 0.001), larger left ventricular diameter (68 [63–73], 67 [58–74], and 62 [56.8–68.3] mm, respectively, P  < 0.001), lower left ventricular ejection fraction (25 [21–30]%, 26 [22–35]%, and 30 [25–38]%, P  < 0.001), and a higher proportion of patients with right ventricular function (48.8%, 40.7%, and 25.9%, P  < 0.001). Patients with Chagas disease were more likely to receive inotropes than patients with non‐Chagas/non‐ischaemic and ischaemic cardiomyopathies (77.5%, 67.5%, and 62.5%, respectively, P  = 0.007) and also to receive intra‐aortic balloon pumping (30.8%, 16.2%, and 10.5%, P  < 0.001). Overall, the rates of death or urgent transplant were higher among patients with Chagas than in other aetiologies, a difference that was driven mostly due to increased rate of heart transplant during hospital admission (20.2%, 10.3%, and 8.1%). The prognosis of patients at 180 days after hospital admission was worse for patients with Chagas disease as compared with other aetiologies. In patients with Chagas, age [odds ratio (OR) = 0.934, confidence interval (CI)95% 0.901–0.982, P  = 0.005], right ventricular dysfunction by echocardiography (OR = 2.68, CI95% 1.055–6.81, P  = 0.016), and urea (OR = 1.009, CI95% 1.001–1.018, P  = 0.038) were significantly associated with prognosis. Conclusions: Patients with Chagas cardiomyopathy and decompensated HF have a distinct clinical presentation and worse prognosis compared with other aetiologies.